Meninjau Tafsir Al-Jawahir Fi Tafsir Al-Qur’an Al-Karim Karya Thanthawi Jauhari Al-Misri: Biografi, Karakteristik, dan Rasionalitas - Ilzam Hubby Dzikrillah Alfani; Mukhsin Mukhsin; Fauzy Ramadhan (Program Studi Ilmu Al-Quran dan Tafsir, 2025)
This paper discusses the biography and thoughts of Thanthawi Jawhari Al-Misri and his tafseer Tafsir Al-Jawahir fi Tafsir Al-Qur'an Al-Karim as one of the interpretations with a scientific pattern. this paper uses a qualitative approach by applying the content analysis method. While the method used by the author is thematic. This type of research is a library study or (library research) which seeks to gather power from various literatures related to the theme of discussion. The data sources used in this study come from library data. This paper tries to conduct a historical study, especially in the field of Qur'anic Sciences and Tafsir by describing Tafsir Al-Jawahir fi Tafsir Al-Qur'an Al-Karim by Sheikh Thanthawi Jauhari Al-Misri which aims to describe the background and thoughts on his interpretation. This discussant concludes Sheikh Thanthawi Jauhari Al-Misri as a Muslim scholar who earned the nickname “Mufassir ilmu” because of the breadth of knowledge he possessed. Sheikh Thanthawi Jauhari Al-Misri has five main sources in his interpretation, namely other Qur'anic verses, Hadith, Qaul of Companions or Tabi'in, science, and previous books. This is evident in one example of the interpretation of QS Ar-Rum/30: 41 which explains about humans and animals as the cause of disasters on land and in the sea.